Respuesta :

We have

(a + bx) / (a - bx) = (b + cx) / (b - cx)

==>   (a + bx) (b - cx) = (a - bx) (b + cx)

==>   ab + (b ² - ac) x - bcx ² = ab + (ac - b ²) x - bcx ²

==>   (b ² - ac) x = (ac - b ²) x

==>   b ² - ac = ac - b ²

==>   2b ² = 2ac

==>   b ² = ac … … … [1]

Similarly, you would find

(a + bx) / (a - bx) = (c + dx) / (c - dx)

==>   ad = bc … … … [2]

and

(b + cx) / (b - cx) = (c + dx) / (c - dx)

==>   c ² = bd … … … [3]

Now:

c ² = bd   ==>   b = c ² / d

b ² = ac   ==>   c = b ² / a

ad = bc   ==>   d = bc / a

and we find

d / c = (bc / a) / (b ² / a) = c / b

and

c / b = (b ² / a) / (c ² / d) = (b ² d) / (a c ²) = b / a

which is to say, the ratio between d and c is equal to the ratio between c and b, and also equal to the ratio between b and a. Therefore (a, b, c, d) are in a geometric progression.